A computational structural analysis of functional attributes of hypodermin A and B proteins: A way forward for vaccine development - Arif, Irum; Siddiqi, Abdul Rauf; Ahmed, Haroon; Afzal, Muhammad Inam; Umer, Muhammad; Maryam, Arooma; Simsek, Sami (Univ Karachi, 2018)
Hypodermosis is a parasitic disease of cattle. The pathogenicity of the disease is attributed to Hypodermin proteins (Hypodermin A, Hypodermin B and Hypodermin C). Studies suggest that Hypodermin proteins may be defined as Serine proteases and collagenases. The structure of both proteases Hypodermin A and Hypodermin B were modeled using the Swiss-model server followed by its validation using Procheck, Errat and Verify-3D. Afterwards, both Hypodermin A and Hypodermin B were docked against collagen in order to study its interaction with respective Hypodermin proteins. The structure of both Hypodermin A and Hypodermin B showed more bent towards hydrophobic nature as more beta sheets were present in them. Both structures were also superimposed to check out similarities and differences present between them. Serine, Aspartic acid, Histidine, Glutamic acid and Lysine are found as interacting residues that are involved in hydrogen bonding with collagen. The interactions are found in the active domain region of Hypodermin proteins. The interacting residues were present in the active region of the hypodermin proteins thus validating the docking studies. This study may help in the drug development against hypodermosis with least side effects.
Keywords: Hypodermosis; hypodermin A; hypodermin B; collagen; modeling; docking